Risk Factors, Clinical Characteristics, and Antibiotic Susceptibility Patterns of Streptococcal Keratitis: An 18-Year Retrospective Study from a Tertiary Hospital in China - Zhen Cheng; Qingquan Shi; Bo Peng; Zijun Zhang; Zhenyu Wei; Zhiqun Wang; Yang Zhang; Kexin Chen; Xizhan Xu; Xinxin Lu; Qingfeng Liang (Antibiotics)
Purpose: Our aim was to investigate risk factors, clinical characteristics, and antibiotic susceptibility patterns of cornea-isolated Streptococcus species collected at a tertiary hospital in China over 18 years. Methods: This retrospective study reviewed data from 350 patients diagnosed with Streptococcal keratitis at Beijing Tongren Hospital between January 2006 and December 2023, including demographics, risk factors, clinical signs, in vivo confocal microscopy (IVCM) imaging, and antibiotic susceptibility testing. Results: The predominant type was Streptococcus pneumoniae (n = 108, 29.8%), followed by Streptococcus mitis (n = 90, 24.9%) and Streptococcus oralis (n = 85, 23.5%). Main risk factors included previous ocular surface disease (24.6%), ocular surgery (21.4%), and trauma (16.3%). Significant differences in clinical characteristics were observed among S. pneumoniae, S. oralis, and S. mitis regarding infiltration location (p = 0.038) and size (p = 0.037), as well as hypopyon presence (p = 0.006). IVCM revealed deeper inflammatory cell distribution and structural disruption as the disease progressed. Resistance rates of aminoglycosides, β-lactams, and fluoroquinolones have increased, with significant differences among species for amikacin (p = 0.010), gentamicin (p = 0.007), and others. Poor outcomes correlated with disease duration over one month, central corneal ulcers, dense infiltrations, hypopyon, and scar tissue presence on IVCM. Conclusions:Streptococcal keratitis is a complex ocular infection with multiple risk factors. S. pneumoniae, S. mitis, and S. oralis are the primary causative agents, exhibiting varying clinical features and antibiotic resistance patterns. Key factors associated with poor outcomes include long disease duration, central corneal ulcers, and severe infiltration.